Pharmacoepidemiological analysis of routine management of heart failure patients in the Russian Federation. Part II - S. V. Nedogoda (Российский кардиологический журнал, 2022)
Aim. To assess the healthcare system costs for the management of patients with heart failure (HF) based on a retrospective analysis of primary medical documentation.Material and methods. We performed the analysis of outpatient records of 1000 patients, followed up for 1 year by a general practitioner or cardiologist in ambulatory clinic in 7 Russian regions. The assessment of the HF socioeconomic burden was carried out from the perspective of the state. A bottom-up approach was applied to the cost analysis. To calculate the average costs per patient per year, the costs for each patient were calculated, followed by estimation for the entire cohort. Direct costs (medical: outpatient care, inpatient care, drug therapy; nonmedical: disability pensions and temporary disability) and indirect costs (loss of gross domestic product) were estimated.Results. It was shown that the average cost of managing 1 HF patient is RUB 160338 per year. The cost of drug therapy varied significantly depending on the source of funding. So, the total therapy cost was about RUB 90000 per year, while within the drug assistance programs — about RUB 7000 per year. Thus, the proportion of drug therapy in cost pattern per patient from the state’s perspective was only 4,7%, while the maximum costs were for inpatient care (45,5%), stay in intensive care units (16,4%) and disability payments (21,6%). The direct costs for HF therapy, with the exception of drug therapy (examination, inpatient and outpatient treatment), averages RUB 108291 per year. The total direct nonmedical and indirect costs per HF patient per year were about RUB 44519 per year. It should be noted that the rehabilitation costs were not included in the calculation.Conclusion. Taking into account the significant burden of HF on the Russian healthcare system, the growing costs of healthcare and the increase in life expectancy, prevention and treatment of HF should be improved. The development of a HF centers’ network, creating a seamless system of HF care, as well as improving the availability of medication therapy and the inpatient management of patients can improve the healthcare quality for HF patients in Russia.